2020
DOI: 10.1002/mrd.23444
|View full text |Cite
|
Sign up to set email alerts
|

A relaxin‐like gonad‐stimulating peptide identified from the starfish Astropecten scoparius

Abstract: A relaxin‐like gonad‐stimulating peptide (RGP) in starfish was the first identified invertebrate gonadotropin responsible for final gamete maturation. An RGP ortholog was newly identified from Astropecten scoparius of the order Paxillosida. The A. scoparius RGP (AscRGP) precursor is encoded by a 354 base pair open reading frame and is a 118 amino acid (aa) protein consisting of a signal peptide (26 aa), B‐chain (21 aa), C‐peptide (47 aa), and A‐chain (24 aa). There are three putative processing sites (Lys‐Arg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…On the other hand, it was revealed that chemically synthesized Asc-RGPs with a nonamidated and amidated C-terminus in the B chain exhibited equivalent induction of oocyte maturation and ovulation in an ovarian fragment of A. scoparius [27,28]. This suggests that C-terminal amidation in the B chain does not affect gonadotropic action in Asc-RGP.…”
Section: Orthologs Of Rgpmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, it was revealed that chemically synthesized Asc-RGPs with a nonamidated and amidated C-terminus in the B chain exhibited equivalent induction of oocyte maturation and ovulation in an ovarian fragment of A. scoparius [27,28]. This suggests that C-terminal amidation in the B chain does not affect gonadotropic action in Asc-RGP.…”
Section: Orthologs Of Rgpmentioning
confidence: 99%
“…The chemical structures of RGP have been identified in several species of starfish, Asterias amurensis (Aam-RGP) [23], Asterias rubens (Aru-RGP) [15,24,25], Aphelasterias japonica (Aja-RGP) [26], Astropecten scoparius (Asc-RGP) [27,28], and the crown-of-thorns starfish (COTS) Achanthaster cf. solaris (Aso-RGP) [29][30][31][32] (Figure 2A).…”
Section: Orthologs Of Rgpmentioning
confidence: 99%
See 3 more Smart Citations